Kontribusi Sektor Pariwisata Halal terhadap Produk Domestik Bruto (PDB) dalam Membangun Perekonomian Berkelanjutan - Sugianto, Sugianto; Zuhra, Sastri Aida; El Alim, Mubarok (Mutawasith: Jurnal Hukum Islam, 2024)
Halal tourism has an important role in sustainable economic growth, especially in countries with a majority Muslim population. Indonesia, as the country with the largest Muslim population, shows rapid growth in the halal tourism industry. This research aims to explore and analyze the contribution of the halal tourism sector to a country's Gross Domestic Product (GDP) in the context of sustainable economic development. This research uses a literature study approach to obtain data from various literature sources, including books and previous research. Data collection techniques involve documentation, where information is obtained from various sources such as notes, books, journals, etc. After the data was collected, descriptive analysis was carried out to reach conclusions. The findings show that halal tourism is increasingly relevant based on Islamic sharia principles as the number of Muslim tourists increases globally. Indonesia is a pioneer in developing halal tourism in Southeast Asia, with a significant contribution to Gross Domestic Product (GDP), halal tourism increases competitiveness and economic growth in the future by implementing industry 4.0 with various digital platforms, halal tourism has a positive impact on the economy by creating new jobs to reduce poverty and improve community welfare.